Fostering knowledge sharing and knowledge utilization: the impact of organizational commitment and trust - Ouakouak, Mohammed Laid; Ouedraogo, Noufou (My University, 2018)
The purpose of this paper is to explore the influence of organizational commitment and trust on knowledge sharing and on knowledge utilization. Also, the study aims to examine the influence of knowledge sharing on knowledge utilization.
Keywords: ethics; knowledge sharing